Film and the digital in visual studies: film studies in the era of convergence - Lisa Cartwright (Journal of Visual Culture 1(1) 2002, 2002)
This article examines how the convergence of various media impacts upon the relations between film studies and visual studies. The questions raised are: How did visual studies emerge as a discipline with film studies in its purview? How does the digital, an aspect of late 20th-century visual culture which emerged roughly simultaneously with visual studies, figure into the field? What happens when film studies is embedded in or combined with visual studies? In acknowledging that visual studies is an outcome of and a response to the conditions of media convergence, this article ends by offering a sense of how questions around optical virtuality and medical imaging can make sense of the effects that media convergence is having on the conditions of experience and subjectivity within modernity.